Urbanization and Extreme Rainfall: A Systematic Review of Global Evidence from Developing and Developed Regions - Faradiba Faradiba (Archives of Current Research International, 2025)
Modern urbanization has become a dominant force in changing the environmental landscape and local climate systems. One of the most visible impacts of this process is the increase in extreme rainfall events in urban areas. This study presents a systematic review of nine academic studies that explicitly examine the relationship between urbanization and extreme rainfall intensity in various parts of the world, both in developed and developing countries. Using the PRISMA-based Systematic Literature Review (SLR) method, hundreds of articles were screened until only nine relevant high-quality studies were left. The results of the review show a consistent pattern that urbanization not only increases the frequency and intensity of extreme rainfall, but also modifies the temporal and spatial distribution of rainfall, strengthens the urban heat island effect, and exacerbates flood and drought risks. These findings emphasize the importance of integrating spatial planning, climate adaptation, and sustainable development policies to anticipate hydrometeorological impacts in urban areas. Further development is expected to consider environmental factors and ecosystem sustainability. This study also fills the gap in the literature by presenting a comprehensive cross-case synthesis as a theoretical and practical basis for future research and policy.